Glossary of terms used in photocatalysis and radiocatalysis, IUPAC Recommendations 2010 - Braslavsky. Silvia; Braun, André; Cassano, Alberto Enrique; Emeline, Alexei; Litter, Marta Irene; Palmisano, Leonardo; Parmon, Valentin; Serpone, Nick (Int Union Pure Applied Chemistry, 2011)
Fil: Braslavsky. Silvia. Institut Max Planck Fuer Bioanorganische Chemie; Alemania